2016
DOI: 10.1016/j.stem.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reprogramming of Hepatic Myofibroblasts into Hepatocytes In Vivo Attenuates Liver Fibrosis

Abstract: Direct induction of induced hepatocytes (iHeps) from fibroblasts holds potential as a strategy for regenerative medicine but until now has only been shown in culture settings. Here, we describe in vivo iHep formation using transcription factor induction and genetic fate tracing in mouse models of chronic liver disease. We show that ectopic expression of the transcription factors FOXA3, GATA4, HNF1A, and HNF4A from a polycistronic lentiviral vector converts mouse myofibroblasts into cells with a hepatocyte phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(130 citation statements)
references
References 34 publications
0
122
0
1
Order By: Relevance
“…Furthermore, GATA4 expression was also reduced in isolated LSECs from a rat cirrhotic liver model (46). As reprogramming of myofibroblasts into hepatocytes by a combination of transcription factors has already been successfully demonstrated to improve liver fibrosis (47,48), prevention and treatment of sinusoidal capillarization by GATA4-mediated reprogramming may soon become reality (49,50). It has recently been shown that single-wall carbon nanotubes are highly promising vehicles for pharmaceutical interventions that preferentially target the hepatic microvasculature via sinusoidal endothelial scavenger receptors STAB1 and STAB2 (51).…”
Section: Author Contributionsmentioning
confidence: 93%
“…Furthermore, GATA4 expression was also reduced in isolated LSECs from a rat cirrhotic liver model (46). As reprogramming of myofibroblasts into hepatocytes by a combination of transcription factors has already been successfully demonstrated to improve liver fibrosis (47,48), prevention and treatment of sinusoidal capillarization by GATA4-mediated reprogramming may soon become reality (49,50). It has recently been shown that single-wall carbon nanotubes are highly promising vehicles for pharmaceutical interventions that preferentially target the hepatic microvasculature via sinusoidal endothelial scavenger receptors STAB1 and STAB2 (51).…”
Section: Author Contributionsmentioning
confidence: 93%
“…More recent study demonstrated that in vivo transcriptional reprogramming by ectopic expression of FOXA3 , GATA4 , HNF1A , and HNF4A transdifferentiates activated HSCs into hepatocyte-like non-fibrogenic cells, namely induced hepatocytes (iHeps), and reduces liver fibrosis [310]. …”
Section: Deactivation and Elimination Of Fibrogenic Hscsmentioning
confidence: 99%
“…In a recent outstanding experimental study Song and coworkers (17) have offered what can be really envisaged as a novel and very promising approach to counteract the progression of CLDs: the establishment of a procedure designed to obtain in vivo direct reprogramming of profibrogenic hepatic myofibroblasts (MFs) into HLCs in fibrotic murine livers (i.e., to concur to repopulate liver parenchyma), that also resulted in a significant attenuation of liver fibrosis. Two nice ideas were at the basis of this study.…”
Section: Editorialmentioning
confidence: 99%
“…Of course, since this can be considered as a pioneer study, there are still limitations as well as unanswered questions, some of these correctly acknowledged by authors (17). A first relevant obvious point relies on the fact that the efficiency of in vivo reprogramming of MFs is still relatively low, and then future studies should pursuit the goal to enhance the overall efficiency of iHep generation, possibly by improving targeted transduction (as Authors themselves suggest), in order to maximize positive effects.…”
Section: Editorialmentioning
confidence: 99%